Strategies to develop the listening skill in nini-year-old primary school studentes - Barros, Marcia Catalina; Pereira Armijos, Karina Elizabeth
The topic of this research is Strategies to develop the listening skill in nine-year-old primary school students. The purpose of this work is to find out strategies in order to create suitable activities tohelp primary school students develop their listening skill inside and outside the EFL (henceforth English as a foreign language) classroom. Richards states listeners can be taught effective ways of approaching and managing their listening (11); for this reason, it is very important to apply the most useful strategies to help students develop this skill. Thus, we have created a booklet with some useful activities that teachers can use with their students (see appendix 4 pag. 39). Since, the listening skill is considered the most important one, it is essential for kids to develop it, so they become good listeners. Thus, the acquisition of the new language will be more productive.